Inovasi Kuliner Ramah Anak di Desa Banjarsari Melalui Pengembangan Produk Tape Mochi Layak Hilirisasi - Eka Putri Surya; Mohamad Firzon Ainur Roziqin; Iriaji; Alby Aruna; Adinda Marcelliantika; Ginanjar Atma Wijaya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The culinary innovation for children in Banjarsari Village through the development of Tape Mochi products suitable for downstreaming aims to enhance the appeal and added value of local products. This program combines traditional and modern methods in creating Tape Mochi, an innovative product that integrates tape as the main ingredient with the child-friendly texture of mochi. Methods include recipe research and development, product trials, technical training for producers, and evaluation through consumer feedback. Results indicate increased interest and satisfaction among consumers regarding Tape Mochi. The implementation of this product is expected to support local culinary diversification, boost the village economy, and introduce children to traditional foods in an engaging manner.